The benefits of performing the split alternating foot snatch - Hedrick, A. (Strength and Conditioning Journal, 2014)
Although the clean is the most commonly performed weightlifting movement in strength and conditioning (s&c) programs, there are also advantages of performing the snatch and its variations when training to improve athletic performance. One variation of the snatch is the split alternating foot snatch (safs). In the safs, the athlete splits the feet to lower themselves under the bar rather than using the squat technique. For most athletes, this split alternating foot technique offers a more sport-specific position than does the more traditional squat position. As a result, there are benefits to including this movement in the training program of athletes.